Data Acquisition System for Efficient L-Band Global Positioning System Signal Reception over a Low Latitude Region - Abba, Ibrahim (unimas, 2016)
Mobile Satellite (MS) signal undergoes attenuation and distortion due to ionospheric, multipath fading and shadowing effects in the transmission path causing irregularities in the received signal quality. Although many studies have been carried out to improve the performance of the mobile satellite (MS) system, there are yet many areas of the less developed and developing countries where satellite data are not available. Furthermore, expensive data acquisition method prevents more studies to be carried out in these countries. In this study, a more economical alternative design for MS data monitoring and mining for the satellites transmitting at L-band was designed, constructed, and implemented by utilizing the Global Positioning System (GPS) data. The research objectives covers the development of data acquisition system for efficient L-band GPS satellite signal analysis, the formulation algorithms for L-band GPS Satellite signal massages as well as the proposed NMEA data extractor for the GPS data acquisition system.